Perlindungan Anak Korban Kekerasan Seksual di Kabupaten Sleman Berdasarkan Undang-Undang Nomor 35 Tahun 2014 - Hesti Rahayu (Jurnal Hukum Lex Generalis, 2025)
The high incidence of sexual violence against children in Sleman Regency indicates that legal protection remains suboptimal. This study aims to analyze the implementation of Law Number 35 of 2014 and the influencing factors, using a normative juridical method. The findings reveal inter-agency synergy involving DP3AP2, the police, and the Social Services, yet effectiveness is hindered by limited human resources, infrastructure, social stigma, and a lack of legal education. Inconsistent interpretation of legal provisions also poses challenges. Strengthened coordination, capacity building for law enforcement, and continuous public education are needed to realize an effective, just, and victim-oriented child protection system.